2020
DOI: 10.1159/000505720
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Cataract Surgery in Eyes with Pseudoexfoliation Syndrome Associated with Weak Zonules: A Case Report

Abstract: A cataract surgery in both eyes was scheduled for an 81-year-old female patient. However, ophthalmic examination revealed marked iridodonesis, phacodonesis and pseudoexfoliative material on the surface of the lens in both eyes indicating weak zonules caused by pseudoexfoliation syndrome, which was more pronounced in the left eye. Cataract surgery was performed initially in the left eye by phacoemulsification. Additionally, iris hooks and capsular tension ring (CTR) were used to stabilize the capsular bag, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 14 publications
0
5
0
3
Order By: Relevance
“…This percentage is higher than observed in our patients; however, Monastam’s study had a longer follow-up period and did not report the actual timing of the late dislocations [ 6 ]. Our patients experienced the first cases of late IOL dislocation within the first three years of follow-up [ 11 ], much earlier than reported for Monastam’s study ( Table 3 ). We expect to find additional dislocations during our continuing follow-up.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…This percentage is higher than observed in our patients; however, Monastam’s study had a longer follow-up period and did not report the actual timing of the late dislocations [ 6 ]. Our patients experienced the first cases of late IOL dislocation within the first three years of follow-up [ 11 ], much earlier than reported for Monastam’s study ( Table 3 ). We expect to find additional dislocations during our continuing follow-up.…”
Section: Discussionmentioning
confidence: 80%
“…Gunenc et al reported two cases of late IOL-CTR-capsular bag dislocations six years after the initial cataract surgery. The article also reported a simple technique for IOL-CTR-capsular bag repositioning by suturing it to the sulcus in twelve o’clock position at the edge of the CTR using 10/0 polypropylene suture [ 52 ]; we used the same approach [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vēlīnās IOL dislokācijas 5 gadu kumulatīvā incidence ir 0,30 % (Clark et al, 2011), 20 gadu kumulatīvā incidence ir ziņota 3 % (Monestam, 2019). IOL-CTRkapsulas maisa vēlīnā dislokācija vairāk ir ziņota kā gadījumu apraksti, parasti notiek 2,5 -8 gadus pēc nekomplicētas kataraktas operācijas ar CTR implantāciju pacientiem ar zonulu vājumu (Kocak et al, 2017;Vanags & Laganovska, 2020). Mönestam ziņo par 2 IOL-CTRkapsulas maisa vēlīno dislokāciju gadījumiem no 11 pacientiem 20 gadu periodā (Monestam, 2019).…”
Section: Vēlīnā Iol Dislokācijaunclassified